Operative lumbar sympathectomy for severe lower limb ischaemia: still a valuable treatment option. - Baker, D. M. (Royal College of Surgeons of England, 1994)
Over a 5-year period, 132 operative lumbar sympathectomies were performed on 118 patients with severe peripheral vascular disease unsuitable for vascular reconstruction. In 62 patients local ulcer débridement or toe amputation was performed at the same time. There was a 45% subsequent limb loss, which occurred predominantly in the first 6 months after sympathectomy. The risk of limb loss was independent of diabetes, hypertension, ischaemic heart disease, cerebrovascular disease or concomitant reconstructive surgery. Of the limbs that survived, rest pain had resolved in 86% within 6 months and 64% recovered from all trophic changes over a similar period. This series suggests that lumbar sympathectomy coupled with local tissue management remains a valuable treatment option for the severely ischaemic limb not amenable to reconstructive surgery.